Beware of What Lurks in the Margin: Glosses, Mobile Digital Games, and Incidental Vocabulary Learning - Rasti-Behbahani, Amin; Abugohar, Mohammed; Khallaf , Nagwa (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The study was set to investigate the effectiveness of meaning-given (meaning-G) and multiple-choice (choice-G) glosses in enhancing incidental vocabulary learning by word learning activities developed with a tablet digital game (DGBVL). Fifty-four Persian speakers (13–14 years old) were divided into meaning, choice, and control (CG) groups randomly after their vocabulary knowledge sizes were measured (2100–2400). After administering two pretests, measuring receptive and productive knowledge of 20 concrete nouns, participants played a commercial adventure game. They read a modified game guide and completed a chapter of the game in pairs. Meaning-G had a single Persian definition, choice-G had three, and CG had none on the page margins. Three weeks later, the participants took post-tests, receptive and productive, without forewarning. Moreover, qualitative data were collected. Results showed that 1) DGBVL activities could enhance incidental learning of the target words regardless of the gloss types; 2) contrary to our expectations, meaning-G enhanced target word productive knowledge acquisition much more effectively than choice-G; and 3) glosses led to different vocabulary learning strategies. This study extends the literature by advising prospective teachers to employ meaning-G to enhance vocabulary acquisition through DGBVL activities effectively.